Pengaruh Earning Per Share (EPS) Dan Debt To Equity Ratio (DER) Terhadap Harga Saham Pada PT Bayu Buana, Tbk. - Jamaluddin, Andi; Hariyanti; Alvia, Karmila (STIM-LPI Makassar, 2024)
The purpose of this research is to determine the effect of Earning Per Share and Debt to Equity Ratio on share prices at PT. Bayu Buana, Tbk. The type of data used in this research is qualitative and quantitative. The data source used in this research is secondary data. The analytical method used is multiple linear regression analysis, coefficient of determination, correlation coefficient, t test, and F test. The results of this study show the regression equation Y=9.139+0.176X1– 0.035X2, coefficient of determination, (R2) = 73% and coefficient correlation (R) = 0.858. through the F test, it is obtained that Fcount = 11.182 > Ftable 4.46, the results of this research show that simultaneously Earning Per Share and Debt to Equity Ratio have a significant effect on share prices at PT. Bayu Buana, Tbk. thus the hypothesis is accepted. Based on the t test b1 tcount = 2.444 > ttable = 1.860, the results of this study indicate that Earning Per Share (X1) partially has a positive and significant effect on share prices so that the hypothesis is accepted. Meanwhile, for b2 tcount = -5,000 < ttable = 1.860, the results of this study show that the Debt to Equity Ratio (X2) partially has a negative and significant effect on stock prices so that the hypothesis is accepted.